A new distinctive species of the genus Orthocladius with hairy eyes from Japan (Diptera: Chironomidae) - Kobayashi, Tadashi (Zootaxa, 2012)
Orthocladius (Euorthocladius) piloculatus sp. nov. is described from Kanagawa Prefecture, Kanto Area, Japan. A char-acter of hairy eyes found in the new species is discussed, and emendations of the generic and subgeneric diagnoses are proposed.